Strategies for Meeting Demand with Fewer Resources - Hauptman, Arthur M. (International Higher Education, 2013)
Virtually all countries around the world are facing the challenge of consistently meeting the rising demand for higher education. A few countries, such as Norway and Saudi Arabia, have decided and been able to devote enough public resources to meet the challenge of adequately funding growing demand. However, for most countries, the challenge remains how to do more, with fewer public resources, to maintain accessible higher education systems of high quality, in the future.